(untitled) (African Multidisciplinary Journal of Research, 2022)
Canonicity refers to the normative or authoritative books inspired by God for inclusion in Holy Scripture. Scripture are sacred texts that serve a variety of purposes in the individual and collective lives of a religious tradition. Scriptures may be used to evoke a deeper connection with the divine, convey spiritual truths, promote mystical experience, foster communal identity, and to guide individual and communal spiritual practice. This paper is a plea to rediscover the essentiality and authority of the Scriptures for an actual Christian life in the world. It begins with some clarification about the locus of authority, and then presents some key issues regarding the authority of Scripture. It is argued that the concept should be understood in close association with the authority of God, the authority of the true story of the world in Jesus Christ, obedience and transformed lives. Throughout the paper, special emphasis is placed on the authority of Scripture as the “living” and “active” word of God for an obedient and transformed Christian living in the world. The research has used conceptual research method which is carried out mainly through study of literature.